Manajemen Pengorganisasian Lembaga Pembelajaran Bahasa Asing Mayantara School - Muthiah Muthiah; Lisnu Afiah; Danial Hilmi (Prodi PBA Fakultas Tarbiyah dan Ilmu Keguruan IAIN Purwokerto, 2020)
Today Language seems to be the prima donna in the eyes of the public, many millennials are interested in learning Foreign Languages. The purpose of them wanting to master the language would be to continue their studies in the country they are aiming for to realize their ideals. Mayantara School is a Foreign Language learning institution that is now a public spotlight in the city of Malang. This institution offers many language programs with a well-organized system and management. This study discusses: 1) Organizing management at Mayantara School course institutions, 2) Division of Tasks in Management Organizing Language Course Institutions at Mayantara School. This research uses descriptive qualitative research methods. Data collection is done by interview techniques and observation and documentation. Data collection is done by reducing data, presenting conclusions / verification data. Research shows that: 1) Mayantara School has a good organizational management system because it has a clear organizational structure. 2) Managers provide division of tasks orally and in writing to each member and create a chart of organizational structure for members so as to make the position between subordinates and superiors visible. Section leaders who have been given certain rights can know the number of clear members to help carry out their duties, so that the organizing system is neatly organized. Keywords: Organizing Management, Mayantara School.